Catalytic converter material treated by ultrasonic approach - Leman, Abd Mutalib (2015)
Automobile catalytic converter is component applied to reduce the pollutant production such as Carbon Monoxide (CO), Nitrogen Oxides (NOx) and Hydro Carbon (HC). Material for catalytic converter is selected. However, the challenge is how to select the right materials and right methods. This research approaches the selective materials such as the γ- Al2O3 nanocrystalline as the washcoat, NiO as the catalyst and FeCrAl as a substrate. Those materials selected since their advantages as described. New method is approached by using combination ultrasonic technique in order to more accelerate the γ- Al2O3 powders. Washcoating process is conducted by using electroplating of Ni plate on FeCrAl substrate by using sulphamate type as electrolyte medium. The potential result is the catalytic converter components provide the oxidation resistance in short term and long term oxidation resistance in high temperature operation as well as improving the homogeneity of material thickness